High-intensity focused ultrasound for endometrial ablation in adenomyosis: a clinical study - Wu, Siyun; Liu, Jun; Liu, Xiaoshan; Han, Yanhua (Frontiers in Medicine, 2024)
The present study aimed to investigate the clinical efficacy of endometrial ablation with highintensity focused ultrasound (HIFU) for symptom relief in women with adenomyosis. Between July 2014 and July 2020, 167 patients with adenomyosis treated at the Zhongshan City People's Hospital were enrolled in this study. Patients were divided into two groups according to patient aspirations: the control group, including patients who only underwent ablation of adenomyosis lesions (group A) and the treatment group, including patients who underwent removal of adenomyosis lesions and endometrial ablation (group B). The reduced dysmenorrhea scores (visual analog scale) and menstrual volume scores (pictorial blood assessment chart) were measured before and after treatment. The scores were obtained by subtracting the postoperative scores from the preoperative scores and were compared to determine whether the symptoms had alleviated. Compared with the menstrual volume of group A, that in group B showed significant improvements. The average relief rates of dysmenorrhea in the two groups also showed significant improvement. However, the scores in group B showed a more significant improvement than those in group A. Therefore, our findings suggest that endometrial ablation using HIFU may be superior to conventional therapy with regard to alleviating the symptoms of increased menstruation in women with adenomyosis.